ANALISIS DAN PERANCANGAN SISTEM INFORMASI KEUANGAN RETRIBUSI PADA BADAN KEUANGAN DAERAH PROVINSI JAMBI - hadi, Irzan; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Regional levies are an important source of regional income to finance the implementation ofgovernment and regional development and to improve service to the community and regionalindependence, that in the framework of implementing regional levies collection techniques needto be regulated as a guideline for collection agencies in accordance with their duties. Retributionthat is currently running at the Jambi Provincial Finance Agency which while in the process ofretribution revenue is still manually experiencing several obstacles such as inaccurate datareported that must wait for all the OPDs of Jambi Province to take a long time which causesdelays to the Regional Finance Agency Jambi Province in calculating the results of the Jambiprovincial retribution income ... to resolve constraints is a system that is capable of processingdata. Here the author designed a new financial information system for levies, while theinformation recommended for Jambi provincial financial institutions consists of admin tables,Retribution Tables, Tourist Tables, Tourist Officer Tables, Visitor Tables, Visit Tables